Deficiency of a novel lncRNA-HRAT protects against myocardial ischemia reperfusion injury by targeting miR-370-3p/RNF41 pathway - Zheng, Xinbin; Zhong, Ting; Yu, Fan; Duan, Jingsi; Tang, Yao; Liu, Yaxiu; Li, Mingrui; Sun, Deqiang; Yin, Deling (Frontiers in Cardiovascular Medicine, 2022)
Accumulating evidence indicates that long non-coding RNAs (lncRNAs) contribute to myocardial ischemia/reperfusion (I/R) injury. However, the underlying mechanisms by which lncRNAs modulate myocardial I/R injury have not been thoroughly examined and require further investigation. A novel lncRNA named lncRNA-hypoxia/reoxygenation (H/R)-associated transcript (lncRNA-HRAT) was identified by RNA sequencing analysis. The expression of lncRNA-HRAT exhibited a significant increase in the I/R mice hearts and cardiomyocytes treated with H/R. LncRNA-HRAT overexpression facilitates H/R-induced cardiomyocyte apoptosis. Furthermore, cardiomyocyte-specific deficiency of lncRNA-HRAT in vivo after I/R decreased creatine kinase (CK) release in the serum, reduced myocardial infarct area, and improved cardiac dysfunction. Molecular mechanistic investigations revealed that lncRNA-HRAT serves as a competing endogenous RNA (ceRNA) of miR-370-3p, thus upregulating the expression of ring finger protein 41 (RNF41), thereby aggravating apoptosis in cardiomyocytes induced by H/R. This study revealed that the lncRNA-HRAT/miR-370-3p/RNF41 pathway regulates cardiomyocyte apoptosis and myocardial injury. These findings suggest that targeted inhibition of lncRNA-HRAT may offer a novel therapeutic method to prevent myocardial I/R injury.